用于印字模切机的控制式差动无级变速器的结构研究及虚拟装配 - 张淳; 赵越 (Jixie chuandong)
The printing die-cutting machine printing roll and cutting stick can be applied to a variety of templates printing,which requires flexible speed and variable speed range.Therefore,the controlled differential CVT（continuously variable transmission）is coupled to the printing die-cutting machine and use its advantage to reach the desired effect.In the process of device structure,by using Pro/E,the virtual assembly is established to test the accuracy and rationality of the parameters,come true parameterization design and improve the efficiency of model analysis.